2013
DOI: 10.1177/0363546513510392
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Femoral Nerve Block in Hip Arthroscopic Surgery

Abstract: A preoperative femoral nerve block is a relatively safe procedure that may decrease the requirement for intraoperative morphine while providing effective postoperative pain control in patients undergoing hip arthroscopic surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
44
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 47 publications
0
44
0
Order By: Relevance
“…Presented at: 31st Annual European Society of Regional Anaesthesia Congress; 2012) 4,28,37 ; and femoral nerve blocks (FNBs). 12,14,44 While paravertebral blocks and lumbar plexus blocks can anesthetize both the obturator and femoral nerves in a single needle pass, these require considerable technical expertise. Fascia iliaca blocks and FNBs take advantage of the fact that the articular branches of the femoral nerve are the predominant contributors to hip joint innervation.…”
mentioning
confidence: 99%
“…Presented at: 31st Annual European Society of Regional Anaesthesia Congress; 2012) 4,28,37 ; and femoral nerve blocks (FNBs). 12,14,44 While paravertebral blocks and lumbar plexus blocks can anesthetize both the obturator and femoral nerves in a single needle pass, these require considerable technical expertise. Fascia iliaca blocks and FNBs take advantage of the fact that the articular branches of the femoral nerve are the predominant contributors to hip joint innervation.…”
mentioning
confidence: 99%
“…Dold et al [20] published a retrospective review of 96 patients, of which 40 received general anesthesia and 56 patients a femoral nerve block preoperatively. A staff anesthesiologist using ultrasound guidance performed all block procedures.…”
Section: Resultsmentioning
confidence: 99%
“…Dold et al [20] reported lower pain scores in the FNB group 60 min after surgery. Total morphine dose in the PACU and maximal pain rating in the surgical day care unit were also significantly lower in the FNB group.…”
Section: Discussionmentioning
confidence: 99%
“…Long-term non-arthroplasty-related pain management is mostly unexplored. To our knowledge, despite the notable escalation in surgery rates, only four studies [811] have discussed pain medication management strategies for non-arthroplasty orthopedic interventions such as FAI. All involved (acute) peri-operative opioid management only.…”
Section: Introductionmentioning
confidence: 99%